Mortality and Rate of Hospitalization in a Colonoscopy Screening Program From a Randomized Health Services Study - Kobiela, Jarek; Spychalski, Piotr; Wieszczy, Paulina; Pisera, Malgorzata; Pilonis, Nastazja; Rupinski, Maciej; Bugajski, Marek; Regula, Jaroslaw; Kaminski, Michal F. (Clinical gastroenterology and hepatology, 2020)
It is difficult to quantify adverse events related to screening colonoscopy due to lack of valid and adequately powered comparison groups. We compared mortality and rate of unplanned hospitalizations among subjects who underwent screening colonoscopies within the Polish Colonoscopy Screening Program (PCSP) vs unscreened matched controls in Poland. Persons 55–64 years old living in the area covered by the PCSP from 2012 through 2015 were assigned in a (1:1) to a group invited for screening colonoscopy (n = 338,477) or a matched group that would be invited 5 years later (controls, n = 338,557). All subjects in the screening group were assigned proposed screening colonoscopy dates (actual dates when invitees confirmed or rescheduled colonoscopy) and those in the control group were assigned virtual dates corresponding to the matched individuals from the screening group. In the screening group, 55,390 subjects (16.4%) underwent screening colonoscopy. Mortality and hospitalization data were obtained from National Registries. We compared mortality and rate of hospitalization between the groups for defined intervals before and after colonoscopy date. Hospitalizations were divided into related and unrelated to colonoscopy based on ICD codes by 3 specialists. Our primary aim was to compare mortality and hospitalization 6 weeks before and 30 days following the actual or virtual date of colonoscopy in the screening or control group. In the intent to treat analysis, overall there were no significant differences in mortality between the colonoscopy group and control group (0.22% vs 0.22%; risk difference less than .01%; 95% CI, decrease of 0.02% to 0.02%; P = .913). The overall rate of unplanned hospitalization was significantly higher for the colonoscopy group (2.39% vs 2.31% for the control group; risk difference, 0.08%; 95% CI, 0.01%–0.15%; P=.026) for the entire observation period. This was due to the higher rate of hospitalizations after screening (1.10% vs 1.01% for the control group; risk difference, 0.09%; 95% CI, 0.04%–0.14%; P < .001) including higher proportion of hospitalizations that were assessed as related to colonoscopy (0.24% vs 0.22% for the control group; risk difference, 0.02%; 95% CI, 0.00%–0.05%; P = .046). In the per-protocol analysis, the overall rate of hospitalizations did not differ significantly between control and screening colonoscopy groups (1.87% vs 1.90%; P=.709). However, screening colonoscopy did increase rates of related hospitalizations after the date of screening (from 0.14% to 0.31%; P < .001). In an analysis of data from the PCSP, we found high-quality evidence that colonoscopy as a screening intervention does not increase mortality before or after colonoscopy. However, it may be associated with a small but significant increase in unplanned hospitalizations, especially after the colonoscopy is completed.